Investigation of the Venom Protein Profile of the Malayan Pit Viper calloselasma rhodostoma (kuhl, 1824) from Vietnam and Toward Toxin Neutralization - Thien, Tao Nguyen; Bao, Minh Vu; Pham Sy, Nhan Nguyen; Thi, Ngoc Anh Trinh; Thanh, Nhan Le; Bao, Yen Pham (VNU Journal of Science: Natural Sciences and Technology, 2025)
Nearly 60 snake species belonging mainly to the Viperidae and Elapidae families are critical threats to human health in Vietnam with thousands of snakebite victims annually. Calloselasma rhodostoma − the Malayan Pit Viper is documented to cause high mortality rates in Southeast Asia. The major components of snake venom include SVMP (Snake Venom Metallo proteinase ) , SVSP (Snake Venom Serine protease), and PLA2 (Phospholipase A2). Information regarding the venom protein composition plays a crucial role in antivenom compound research and development. However, currently, there is no study carried out to investigate these major toxins and their activities in the Malayan pit viper in Vietnam. Using consecutive differential centrifugation, SDS−PAGE analysis, and plate diffusion assay, we demonstrated the presence of several proteases in the venom of C. rhodostoma from Vietnam. In the supernatant fractions, five dominant bands predicted to represent groups of SVMPs, PLA2, SVSP could be observed. Three concentrated fractions, C100, C50, and C10 showed proteolytic activity with the largest substrate clear zone belonging to the fraction containing higher molecular weight SVMPs. This study provided for the first time evidence of venom toxins ’ presence in the venom of the Malayan pit viper from Vietnam and their activity towards the screening of antivenom drugs .